2008
DOI: 10.5650/jos.57.353
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Inactivation with Colloidal Silica

Abstract: We evaluated the allergen inactivating effect of colloidal silica by performing enzyme-liked immunosorbent assay (ELISA) whose wells were coated with 150 ng/mL of Japanese cedar pollen allergen (Cry j 1) or mite allergen (Der f 2). The allergens were almost 100% inactivated by 100 microg/mL of colloidal silica having a particle size 5 nm, and the inactivating effect was increased by aluminum binding to the surface of the colloidal silica. The results show that colloidal silica is a promising material for aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported methods of xenobiotic reduction using corona discharge, ions generated by plasma discharge, colloidal silica and hypochlorous acid. 3135 Additionally, we suggest usefulness of streamer discharge as one of xenobiotic reduction technologies.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported methods of xenobiotic reduction using corona discharge, ions generated by plasma discharge, colloidal silica and hypochlorous acid. 3135 Additionally, we suggest usefulness of streamer discharge as one of xenobiotic reduction technologies.…”
Section: Discussionmentioning
confidence: 91%